1983
DOI: 10.1007/bf02926806
|View full text |Cite
|
Sign up to set email alerts
|

Radiology of obstetric vesicovaginal fistula

Abstract: The excretory urograms of 70 Nigerian women presenting to the University of Benin Teaching Hospital with obstetric vesicovaginal fistula over a 7-year period are analyzed. The common abnormalities are medial deviation of distal ends of ureters (34%); discrete but smooth pseudoprostatic bladder base indentation (33%); and calyceal clubbing of varying degrees (19%). Other abnormalities observed include hydroureters (18%); bladder calculi (7%); bladder wall calcification (3%), and unilateral nonfunctioning kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The appearances of the upper urinary tract on sonography as observed in this study and on IVU as described previously 6,7 are not pathognomonic for obstetric fistulae as these appearances are well observed in other causes of lower urinary tract obstruction or infection. Therefore, in terms of the assessment of structural abnormalities, sonography is well suited, and the physiologic status of the kidneys could be assessed by the serum levels of electrolytes and urea.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The appearances of the upper urinary tract on sonography as observed in this study and on IVU as described previously 6,7 are not pathognomonic for obstetric fistulae as these appearances are well observed in other causes of lower urinary tract obstruction or infection. Therefore, in terms of the assessment of structural abnormalities, sonography is well suited, and the physiologic status of the kidneys could be assessed by the serum levels of electrolytes and urea.…”
Section: Discussionsupporting
confidence: 82%
“…Previously radiography either was unable to identify a definite fistulous track 7 as demonstrated by IVU in this study or was only able to show the fistula as a midline "opacity-within-an-opacity." 6 The exact location and size are infrequently seen in these conventional ways, but sonography has been able to demonstrate the course, site, and size of the fistula in about one third of the cases.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In patients with obstetric VVFs, other IVU abnormal- ities such as medial deviation of the pelvic ureters and pseudoprostatic bladder base indentation may be seen; there may also be bone changes, particularly osteophyte formation on the superior pubic ramus. 5 Computerized tomography may reveal contrast-opacified urine pooling within the vagina, but spatial and contrast resolution are too poor to permit visualization of the fistulous tract.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Akamaguna et al; found that stones were found only in 7% of VVF cases on radiological evaluation. [8] The presentation of VVS may vary from suprapubic pain,repeated urinary tract infections,pyuria,dysuria,,hematuria and urinary leakage. For diagnosis of VVS only pervaginal examination is required without need of any investigations.…”
Section: Introductionmentioning
confidence: 99%